PENGEMBANGAN MODUL PRAKTIKUM BERBASIS PAIKEM PADA MATERI FISIKA SMA KELAS X SEMESTER II - Dasril, Dasril; Yulkifli, Yulkifli; Haris, Venny (Jurnal Pembelajaran MIPA, 2014)
Its is hard adjusted learning execution time with practicums performing, making difficult experiment is done at school. experiment also havent made active student, so required by experimentâs module gets PAIKEMS basis in lead experimentâs performing. The purpose of this Research is result practicum module that valid and practical. Observational method is 4D. Observational step that is done is problem Identification, information gathering, product design, validate design, fixed up design and product test-driving. This research result experiment module gets PAIKEMS basis that valid, with validity zoom 80%.Key words: development, module, paikem, validite, practice